2007
DOI: 10.1016/j.schres.2007.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine consumption and schizotypy in first-degree relatives of individuals with schizophrenia and non-psychiatric controls

Abstract: Individuals with schizophrenia have very high rates of cigarette smoking, and much has been discovered about the influence of nicotine on brain functioning in schizophrenia. However, less is understood about the relationship between nicotine consumption and milder phenotypes related to schizophrenia, specifically schizotypy. This study examined the relationship between nicotine consumption and schizotypy in two unmedicated samples that included first-degree relatives and non-psychiatric controls.Forty-two firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 48 publications
(44 reference statements)
2
29
1
1
Order By: Relevance
“…Third, frequency/amount of alcohol use in the 25 to 29-year age range was directly correlated with current SPQ cognitive-perceptual, interpersonal, and total scores, frequency/amount of cannabis use in the 20 to 24-year age range was directly correlated with the SPQ interpersonal score, and all four SPQ scores were significantly and strongly directly associated with frequency/amount of cannabis use in the 25 to 29-year age range. These results suggest that the use of addictive substances, particularly cannabis (but also nicotine, based on previous findings reported by Esterberg and associates [27]), is related to schizotypy in complex ways. Greater elucidation of these associations, ideally using longitudinal research designs, could provide crucial information not only on the connection between substance use and schizotypy, but between substance use and schizophrenia.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Third, frequency/amount of alcohol use in the 25 to 29-year age range was directly correlated with current SPQ cognitive-perceptual, interpersonal, and total scores, frequency/amount of cannabis use in the 20 to 24-year age range was directly correlated with the SPQ interpersonal score, and all four SPQ scores were significantly and strongly directly associated with frequency/amount of cannabis use in the 25 to 29-year age range. These results suggest that the use of addictive substances, particularly cannabis (but also nicotine, based on previous findings reported by Esterberg and associates [27]), is related to schizotypy in complex ways. Greater elucidation of these associations, ideally using longitudinal research designs, could provide crucial information not only on the connection between substance use and schizotypy, but between substance use and schizophrenia.…”
Section: Discussionsupporting
confidence: 83%
“…The interviewer continued with subsequent age periods following the same procedure. For example, if a 35-year-old participant reported that he/she began smoking cannabis at age 16 years, the interviewer asked the participant to give an average frequency (per month) and the amount in joint equivalents (per usage) for ages 16-19 years, and then asked about average frequency and amount for the next two age periods (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Amounts were designated by units, such that one unit of alcohol equaled one beer, glass of wine, liquor drink, or shot; one unit of cannabis equaled one joint; and one unit of crack cocaine equaled one rock.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the use of this group also allows differentiation between specific traits and symptoms associated with schizophrenia and their impacts on the ability in question 26,[31][32][33] .…”
Section: Introductionmentioning
confidence: 99%
“…30 Furthermore, a positive relationship was found between smoking status and level of schizotypy, where higher levels of schizotypy significantly predicted the risk of being a smoker after controlling for gender and group status. 31 Heavy smoking in patients has been regarded as an attempt of self-medication and there is evidence that nicotinic agonists improve clinical ratings of negative symptoms that are generally resistant to treatment with dopamine antagonist anti-psychotic drugs. 32 This implies that cigarette compounds may activate compensatory or beneficial mechanisms ameliorating the pathophysiology of the disease.…”
Section: Discussionmentioning
confidence: 99%